Nonlinear optical potassium niobate nanocrystals as harmonic markers: the role of precursors and stoichiometry in hydrothermal synthesis. Issue 22 (30th May 2018) - Wang, Zunhao; Kijatkin, Christian; Urban, Alexander; Haase, Markus; Imlau, Mirco; Kömpe, Karsten
Abstract : Hydrothermal synthesis of KNbO3 leads to crystallite sizes down to 30 nm. They exhibit significant SHG-signals throughout the visible range. Abstract : Nanocrystals of alkaline niobates are currently being discussed for various applications because of their diverse and remarkable properties. Although the growth of bulk niobate crystals is well established, little is known about respective nanocrystals and the optical properties of niobates below 100 nm. A systematic view of the hydrothermal synthesis of potassium niobate with respect to the precursor species reveals the sensitive dependence of the resulting crystalline phases and sizes on the educt modifications. With a variation of stoichiometry of the procedure, the product modification and crystallite size can be changed. By means of second harmonic generation, nanocrystalline potassium niobate offers the possibility for use as an optical marker in high resolution nonlinear microscopy. Redispersed particles show a significant second harmonic generation signal throughout the visible spectral range.